45 degree arrangement of compact array antenna for MIMO application - M. F. Ismail; H. A. Majid; C. Macwright; M. N. A. H. Shaabani; M. S. Mohd; M. M. Zahar; F. Zubir; M. A. Abdullah (Institute of Advanced Engineering and Science, 2019)
A study on the compact array microstrip patch antenna for multiple-input multiple-output (MIMO) communication system based on the antenna arrangement is performed. The 2.45 GHz rectangular array are arranged in 45 degree slanted inward and outward for each other to reduce the mutual coupling effect between the patches. The antenna properties are analyzed and compact antenna design is determined based on the simulation results. The results show the antennas can very compact while maintaining low mutual coupling. The gain of the MIMO antenna is 11.3 dBi. The simulated and tested return losses, together with the radiation patterns, are presented and discussed.